Інституту мистецтвознавства, фольклористики та етнології ім. М. Т. Рильського НАН України - 85 років - Скрипник, Г. (Народна творчість та етнографія, 2006)
This article is devoted to the 85-th anniversary of the Rylsky Institute of Art studies, Folklore and Ethnology. The author retrances a long and not easy formation route from the art study sells to the leading field institution. Valuation of science establishment's activity at different periods of its historical development is also given in the article.